Hansel and Gretel - Kelly; Miles (Essex Miles Kelly, 2015)
Siblings Hansel and Gretel are abandoned in the forest by their parents. They stumble upon a house made of candy, owned by a wicked witch who captures them. Using their wits, they outsmart the witch and find their way back home.